2022
DOI: 10.3390/ijerph19010541
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Alteration in the Plasma of Wild Rodents Environmentally Exposed to Lead: A Preliminary Study

Abstract: Lead poisoning is often considered a traditional disease; however, the specific mechanism of toxicity remains unclear. The study of Pb-induced alterations in cellular metabolic pathways is important to understand the biological response and disorders associated with environmental exposure to lead. Metabolomics studies have recently been paid considerable attention to understand in detail the biological response to lead exposure and the associated toxicity mechanisms. In the present study, wild rodents collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It acts similar to calcium in the body and builds up in the kidney, the liver, and other tissues (96,97). Clinically, poisoned cattle typically exhibit indications of malnutrition, emaciation, muscle loss, aberrant fetal development, opaque hair, and moderate anemia and thickening of phalange epiphyses (78,98,99). Additionally, according to other studies, Pb-poisoned cattle exhibit ataxia, paresis of the hypoglossal nerve, severe depression, muscle twitching, convulsions, coma, death, and respiratory failure (83, 100).…”
Section: E Ect Of Lead On Cattlementioning
confidence: 99%
See 2 more Smart Citations
“…It acts similar to calcium in the body and builds up in the kidney, the liver, and other tissues (96,97). Clinically, poisoned cattle typically exhibit indications of malnutrition, emaciation, muscle loss, aberrant fetal development, opaque hair, and moderate anemia and thickening of phalange epiphyses (78,98,99). Additionally, according to other studies, Pb-poisoned cattle exhibit ataxia, paresis of the hypoglossal nerve, severe depression, muscle twitching, convulsions, coma, death, and respiratory failure (83, 100).…”
Section: E Ect Of Lead On Cattlementioning
confidence: 99%
“…Pb is considered one of the major environmental toxins in industrial areas of the world and animals are frequently exposed to it ( 78 , 79 ). Numerous environmental factors including industrial pollution, agricultural practices ( 80 ), cosmetics, automobiles, paints, and contaminated feed and soil ( Figure 2 ) can cause Pb poisoning, which is especially common in animals ( 81 , 82 ).…”
Section: Heavy Metals: Their Toxicity Mechanism and Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that Pb concentrations in incisor crowns may reflect Pb contamination in rat habitats and may serve as a new monitoring indicator. The most recent report on rodents concerns the effects of Pb exposure on metabolism (Nakata et al, 2022). In this study, metabolomic analysis of plasma was performed using the gas chromatography-mass spectrometry (GC-MS).…”
Section: Animal Studiesmentioning
confidence: 99%
“…e new curriculum standard of college English requires teachers to change the traditional teaching style, optimize students' English learning style, and strengthen the cultivation of students' learning strategies so as to improve their learning ability [3]. However, because of the impact of traditional English education, the English learning environment in colleges has certain problems in terms of physical and psychological environment that need to be solved as soon as possible [4].…”
Section: Introductionmentioning
confidence: 99%